2017
DOI: 10.3389/fpls.2016.02054
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Chloroplast Genomes of Three Cardiocrinum (Liliaceae) Species: Comparative Genomic and Phylogenetic Analyses

Abstract: The genus Cardiocrinum (Endlicher) Lindley (Liliaceae) comprises three herbaceous perennial species that are distributed in East Asian temperate-deciduous forests. Although all three Cardiocrinum species have horticultural and medical uses, studies related to species identification and molecular phylogenetic analysis of this genus have not been reported. Here, we report the complete chloroplast (cp) sequences of each Cardiocrinum species using Illumina paired-end sequencing technology. The cp genomes of C. gig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(143 citation statements)
references
References 61 publications
29
106
0
Order By: Relevance
“…Besides, they found that infA existed but seemed to have lost its function in the Lilium (Liliaceae) cp genome, because it had AAT instead of ATG in the start codon position and includes two premature stop codons. The pseudogenization of infA was also found in Fritillaria (Li et al, 2014) and Cardiocrinum (Lu et al, 2016), close relatives of Lilium . However, our study indicates the loss of infA in Amana .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Besides, they found that infA existed but seemed to have lost its function in the Lilium (Liliaceae) cp genome, because it had AAT instead of ATG in the start codon position and includes two premature stop codons. The pseudogenization of infA was also found in Fritillaria (Li et al, 2014) and Cardiocrinum (Lu et al, 2016), close relatives of Lilium . However, our study indicates the loss of infA in Amana .…”
Section: Discussionmentioning
confidence: 77%
“…This is congruent with a typical monocot cp genome structure (Yang et al, 2013). Among other taxa in the family Liliaceae, IR expansion into rps19 has been observed in Lilium (Kim and Kim, 2013), Fritillaria (Li et al, 2014), and Cardiocrinum (Lu et al, 2016). This suggests that the expansion of the IR/LSC junctions into rps19 may be an ancestral symplesiomorphy of the family Liliaceae, and thus provides no relevant phylogenetic information for addressing intrafamilial questions.…”
Section: Discussionmentioning
confidence: 99%
“…The intergenic spacer ycf3-trnS has been used in phylogenetic inferences in Asteraceae and Euphorbiaceae (Vilatersana et al 2010;Montes Moreno et al 2010; Barres et al 2011), and the rps3 gene in Poaceae, Verbenaceae and families of Asparagales (Peterson et al 2010;Marx et al 2010;Kim et al 2012). The intergenic spacer ndhE-psaC appears to have not yet been used as a marker for phylogenetic studies, but it was also reported as useful for phylogenetic and phylogeographic studies in Liliaceae (Lu et al 2017). The intergenic spacer ndhC-rbcL is putatively exclusive of Cactaceae, resulting from the trnV-rbcL inversion, and its phylogenetic utility must be further investigated, at least in clades where ndh genes are present.…”
Section: Phylogenetically Informative Regionsmentioning
confidence: 99%
“…In the present study, because we conducted field experiments and sampling of material in Hokkaido, we treated the study species as C. cordatum var. glehnii (Lu, Li, & Qui, 2017).…”
Section: Methodsmentioning
confidence: 99%